2005
DOI: 10.1086/430709
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Lamivudine in Salvage Therapy for Multidrug‐Resistant HIV‐1 Infection

Abstract: In select cases of multidrug-resistant HIV-1 infection, lamivudine contributes to suppression of HIV-1 replication, despite the presence of M184V mutations and lamivudine resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 20 publications
3
62
2
3
Order By: Relevance
“…However, the loss of M184V occurred well after the rise in viral load, suggesting that the residual antiviral activity of nucleosides, rather than an increase in viral fitness, was the cause of the viral rebound (38). Similar observations were made in nonrandomized studies of lamivudine or lamivudine-zidovudine interruption (28,59). Selective interruption of the fusion inhibitor enfuvirtide leads to prompt but limited increases in viral load (ϳ0.1 to 0.2 log 10 copies/ml), indicating that this drug also has some limited efficacy despite the presence of drug-resistant variants (39).…”
Section: Outcomes In Chronic Hiv-1 Infectionsupporting
confidence: 54%
See 1 more Smart Citation
“…However, the loss of M184V occurred well after the rise in viral load, suggesting that the residual antiviral activity of nucleosides, rather than an increase in viral fitness, was the cause of the viral rebound (38). Similar observations were made in nonrandomized studies of lamivudine or lamivudine-zidovudine interruption (28,59). Selective interruption of the fusion inhibitor enfuvirtide leads to prompt but limited increases in viral load (ϳ0.1 to 0.2 log 10 copies/ml), indicating that this drug also has some limited efficacy despite the presence of drug-resistant variants (39).…”
Section: Outcomes In Chronic Hiv-1 Infectionsupporting
confidence: 54%
“…However, other studies have shown that lamivudine does exert some antiretroviral effect on the M184V mutant, suggesting that the incomplete viral rebounds that occur may represent residual antiviral activity rather than selection for a mutant with reduced fitness (139). Studies of selective lamivudine treatment interruptions demonstrate increases in viral load before reversion of the M184V mutant, also supporting the hypothesis that lamivudine retains antiretroviral activity against M184V (28).…”
Section: Mutations Conferring Resistance To Reversementioning
confidence: 75%
“…HIV-1 mutants with diminished replication fitness have been known to provide clinical benefit in practice. For example, many clinicians have chosen to continue to use 3TC even after the 3TC resistance mutation M184V has emerged to take advantage of the viral replicative defect caused by this mutation (18).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, individuals with documented drug resistance have lower levels of CD4 ϩ and CD8 ϩ T cell activation, experience lower rates of CD4 ϩ depletion, and progress more slowly to AIDS than do untreated HIV-infected individuals, independently of plasma HIV RNA levels (28)(29)(30)(31)(32). The reduced ability of drug-resistant viruses to contribute to disease progression may result from particular drug resistance mutations that impede viral replicative capacity, thus decreasing the activation of bystander T cells (29,33). Conversely, the presence of CXCR4-tropic viruses was associated with higher levels of inflammatory markers in one study (34) but with no difference in levels of inflammatory markers in another (35).…”
mentioning
confidence: 99%